Association between ambient temperature and semen quality: A longitudinal study of 10 802 men in China. (February 2020) - Zhou, Yun; Meng, Tianqing; Wu, Li; Duan, Yonggang; Li, Guo; Shi, Chunxiang; Zhang, Hai; Peng, Zhe; Fan, Chuangang; Ma, Jixuan; Xiong, Chengliang; Bao, Wei; et al.
Graphical abstract: Highlights: We found an inverted U-shaped association of ambient temperature with semen quality. Both low and high ambient temperatures were inversely associated with semen quality. An "optimal" ambient air temperature of 13 °C was suggested for semen quality. Abstract: Semen quality is a vital determinant for male fertility. The process of spermatogenesis is highly sensitive to fluctuations in temperature. However, the impact of ambient temperature on semen quality remains unclear. We aimed to quantitatively assess the association between ambient temperature and semen quality. Using data from Hubei provincial human sperm bank in Wuhan, China, we conducted a longitudinal study including 10 802 volunteers who lived in Wuhan and passed the initial physical examination for sperm donation between Mar 27, 2013 and April 9, 2018. Semen quality parameters including sperm concentration, total sperm number, total motility, progressive motility, total motile sperm count and progressively motile sperm count were determined in the sperm bank. We used linear mixed models to identify estimate changes of outcomes in relation to ambient temperature (i.e., air temperature and apparent temperature) exposure measured as the mean daily temperature during the 0–90 days before semen collection. Among 10 802 subjects who underwent 41 689 semen examinations, we observed inverted U-shaped exposure-response associations between air temperature exposure and all semen quality parameters, with an identical threshold exposure of 13 °C. For air temperature exposure <13 °C, each 5 °C lower temperature was significantly associated with 1.94 × 10 6 /ml, 7.12 × 10 6, 0.77%, 0.81%, 6.48 × 10 6, and 5.87 × 10 6 decrease in sperm concentration, total sperm count, total motility, progressive motility, total motile sperm count and progressively motile sperm count, respectively. When air temperature exposure was ≥13 °C, each 5 °C higher temperature was significantly associated with 0.70 × 10 6 /ml, 4.09 × 10 6, 1.01%, 1.06%, 4.31 × 10 6, and 4.20 × 10 6 decrease in sperm concentration, total sperm count, total motility, progressive motility, total motile sperm count and progressively motile sperm count, respectively. Age, BMI and smoking did not significantly modify these associations. Similar results were observed for apparent temperature. This study provides a comprehensive picture of nonlinear association between ambient temperature and semen quality, as well as an optimal temperature for the benefit of semen quality. Both lower and higher ambient temperature exposures compared with the optimal temperature were significantly associated with decreased semen quality. The findings highlight the needs and importance to reduce extreme ambient temperature exposures in maintaining optimal semen quality for men. Further investigation is warranted to determine the causality of the association and the underlying mechanisms.